EFFECT OF PRELOAD OF ANGULAR CONTACT BALL BEARINGS ON LIFE OF BEARINGS - Andrzej RACZYŃSKI; Jarosław KACZOR (Scientific Journal of Silesian University of Technology. Series Transport, 2014)
Angular contact ball bearings are commonly used in such situations when you need to reach high bearing stiffness. However, a significant stiffness increase can be achieved only through the introduction of preload to the angular contact bearings. The purpose of this paper is to present a method for assessing the effect of preload of the angular contact bearings for their durability.